Social media among homosexuals: A new era of gay life in the age of technology - Mustangin Mustangin (Faculty of Social and Political Science, Universitas Airlangga, 2018)
The gay community in Indonesia is still considered to be a minority and not widely accepted by the general public. Therefore, many of gay individuals are looking for an alternative to be able to meet others through a community. Furthermore, the development of the media nowadays has contributed to the emergence of numerous social media created specifically for homosexuals to meet each one another. This study aims to reveal the phenomenon of social media specifically created for gay men, including the nature of the activities carried out and its purpose for the gay community. This study is a qualitative research study, conducted using a case study. This study found that social media specifically created for gay men is used as a tool to make friends, to communicate, and to be socially accepted. Their activity on social media is initiated with an introduction, similar to other social media. However, this social media possesses a gay radar that enables the user to find fellow gay men in their surroundings. The emergence of this gay-specific social media is a phenomenon caused by the development of technology. This particular form of social media is utilized by the gay community to interact with one another and to let their identity as a human to be acknowledged.